The Employment Effects of Renewable Energy Consumption in Sub-Saharan Africa - Mazorodze, Brian Tavonga (International Journal of Energy Economics and Policy, 2025)
The global shift from fossil fuels to renewable energy has spurred interest among policymakers in understanding its impact on jobs particularly in low-income regions such as sub-Saharan Africa. Against this background, this study examines the relationship between renewable energy consumption and employment in sub-Saharan Africa (SSA) using a panel dataset comprising 30 countries observed between 1992 and 2020. Results from the Pooled Mean Group (PMG) estimator show that renewable energy consumption has a positive long-run impact on overall employment, with a percentage point increase in renewable energy consumption estimated to raise employment by 0.37 percentage points. The effect, however, varies across sectors. Renewable energy particularly benefits agricultural employment while shrinking employment in the industry and service sectors. The model estimates a 0.72 percentage points increase in agricultural employment in response to a percentage point expansion in renewable energy consumption. In contrast, employment in the industry and service sectors falls by 0.13 and 0.34 percentage points, respectively. An alternative estimator that explicitly handles endogeneity reaches a similar conclusion. The results highlight the need for complementary measures, such as skills development programs and sector-specific interventions, to ensure inclusive and sustainable employment outcomes in sub-Saharan Africa’s energy transition.